Diabetic Ketoacidosis Occurring in Patient on Newly Started Insulin Glargine U300 - Kıraç, Cem Onur; İpekçi, Süleyman Hilmi; Kebapcılar, Levent (European Journal of Therapeutics, 2023)
Insulin glargine U300 is a 3-fold, concentrated, long-acting insulin analog providing a more stable effect compared with insulin glargine U100. However, stable plasma insulin concentration is reached on day 4 of the treatment. Patients with type 1 and type 2 diabetes mellitus with decreased insulin reserve are at an increased risk of diabetic ketoacidosis when there is insufficient exogenous plasma insulin concentration. Herein, we present a case of diabetic ketoacidosis occurring in a patient with insulin glargine U300 and emphasize the pharmacokinetic properties of insulin glargine U300.